DEVELOPING A COMPUTER PROGRAM FOR MODELING THE STADIA MEASUREMENTS FOR TACHEOMETRY WORKS (Journal of Engineering, 2009)
Tacheometry is used to measure the lengths of traverse sides, to check the more accurate taped distances in order to uncover gross errors or mistakes and to determine differences of elevation between points. It's most general use is found in the compilation of planimetric and topographic maps by field methods alone, by which distances, elevations and directions to points are to be determined from field control points whose positions have been established by a higher order of accuracy. The principles of stadia measurement by use of the transit or theodolite or total station is one of the main method of tacheometry. This paper presents the principles of stadia measurement and a computer program MSM (Modeling the Stadia Measurements). The program is formulated and written by using the Visual Basic language, Version 6. This version of the language is objecting oriented provided with comprehensive tools to simplify the task of programming and to provide the programmer with wide range of options for design of the user interface system.